MORPHOLOGICAL AWARENESS IN STUDENTS’ READING COMPREHENSION: A CONNECTION WITH PHONICS INSTRUCTION - Rayhan Khairunnisa Situmorang; Ratna Dewanti (Wiralodra English Journal, 2025)
The ability to read and learn a language is connected to morphological awareness. This research examines students’ understanding of morpheme identification, morphological structural awareness, and reading comprehension for EFL students using morphological awareness tests, reading comprehension tests, and video analysis. The video analysis focuses on phonics instruction, a process of teaching reading in which students learn to match sounds to letters, highlighting its potential to enhance morphological awareness. The findings show that students who perform well on morphological awareness tests also score higher on reading comprehension tests. The analysis of the video on phonics instruction reveals its role in enhancing morphological awareness through repetitive activities. These results emphasize the importance of integrating phonics instruction to develop morphological awareness and improve reading comprehension. A mixed-methods approach was employed, resulting in both quantitative and qualitative data. Quantitative data were obtained from morphological awareness and reading comprehension tests, while qualitative data were gathered from video analysis on a YouTube channel.